2019
DOI: 10.4038/cmj.v64i3.8950
|View full text |Cite
|
Sign up to set email alerts
|

Body image perception and body dissatisfaction among rural Sri Lankan adolescents; do they have a better understanding about their weight?

Abstract: Introduction Adolescents have high vulnerability for body image distortions which may result in many psychological and physical problems.Objectives This study aimed to determine body image perception and dissatisfaction among rural schooling adolescents in Sri Lanka.Methods Adolescents (aged 13-16 years) were selected using probability-based sampling framework. Selfadministered figure rating scale was used to assess perceived current (PCBS) and ideal (IBS) body size and body discrepancy score (BDS = PCBS -IBS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Adolescence is a critical period for body image development because of the various social, cultural, physical, and psychological changes occurring between the ages of 12 years and 18 years. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is a critical period for body image development because of the various social, cultural, physical, and psychological changes occurring between the ages of 12 years and 18 years. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…Body image can be modulated by different aspects of social media; adolescents have access to information on the Internet that can give a distorted view of normality and they are often bombarded with increasingly extreme images. 6 7 8 9 10 11 12 …”
Section: Introductionmentioning
confidence: 99%
“…Simple logistic regression analysis was used to examine the determinants of dissatisfaction. Independent variables were gender, father's occupation (socioeconomic status proxy variable), ethnicity as per prior knowledge [10,18]. All variables with a p-value less than 0.1 were included in multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies had reported regional differences (rural vs. urban) in body image dissatisfaction [8]. It appears that effect of many other factors such as socioeconomic position and gender are still unclear [9,10,11]. In a study among Sri Lankan rural adolescents, males had poor satisfaction compared to females [10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation